Applying Scientific Reasoning to the Field of Marketing - Grapentine, Terry (Business Expert Press, 2012)
Ebook from IG Library ; Marketing decisions often misfire when driven more by beliefs than knowledge. Make Better Marketing Decisions: Lessons from the Philosophy of Science, guides readers on how to think more clearly and correctly when making these decisions, thereby increasing organizational success. The book is based on the field of epistemology--the study of how knowledge is created--within the philosophy of science. Epistemology is a difficult subject with its own vocabulary and concepts that are often esoteric and considered too academic for marketing decision makers and researchers to apply. Consequently, the first sections of the book disabuse this notion by explaining why incorporating a scientific way of viewing the world and the scientific method is actually a practical way to make better decisions. These introductory chapters transition into a more formal discussion of philosophy of science, epistemology, and why marketing is a social science as opposed to merely an art or a practice, like medicine or engineering. The main body of the book then guides the reader through selected lessons from the philosophy of science to improve decision making. Example topics are (1) applying scientific reasoning to decision making, (2) differentiating between symptoms vs. causes of consumer behavior, and (3) understanding the importance of theory development in translating information into understanding. The book concludes by identifying the necessary conditions for applying philosophy of science's lessons to decision making and how to strike the proper balance between (1) allocating resources for knowledge creation, and (2) managing the day-to-day realities of running a business.